Digital nomads for dummies - Wilson, Kristin M. (Tantor Media, Inc., 2022)
Why work from home when you can work anywhere? Not all who wander are lost! Digital Nomads For Dummies answers all your questions about living and working away from home, short term or long term. Become a globetrotter or just trot around your home country, with the help of experienced digital nomad Kristin Wilson. Millions of people have already embraced the lifestyle, moving around as the spirit takes them, exploring new places while holding down a job and building a fantastic career. Learn the tricks of building a nomad mindset, keeping your income flowing, creating a relocation plan, and enjoying the wonders of the world around you. - Learn what digital nomadism is and whether it's the right lifestyle for you - Uncover tips and ideas for keeping travel fun while holding down a nine-to-five - Travel solo or with a family, internationally or within your home country - Create a plan so you can keep growing in your career, no matter where you are If you're ready to put the office life behind you and the open road in front of you, check out Digital Nomads For Dummies and get your adventure started!
Online resource; title from title details screen (O'Reilly, viewed September 20, 2022)
Keywords: Travelers -- Employment; Telecommuting; Voyageurs; Travail; Downloadable audio books; Audiobooks; Livres audio